2010
DOI: 10.1111/j.1755-3768.2008.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of intraocular pressure reduction on the occurrence of glaucoma

Abstract: ABSTRACT.Purpose: To estimate the effect of reducing intraocular pressure (IOP) on: (i) the incidence of primary open-angle glaucoma (POAG) in patients with ocular hypertension (OH), and (ii) the progression of glaucoma. Methods: A meta-analysis of relevant randomized controlled trials was conducted. A literature search was performed to identify trials with: a randomized comparison of IOP-lowering intervention versus placebo or no treatment; visual field loss or optic disc changes as outcome; and follow-up >6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…More relevant, however, is the fact that visual field loss is related to vision and health-related quality-oflife (HRQOL), which directly reflect patients' experiences. [1][2][3][4][5] Ultimately the aim of glaucoma treatment is to prevent HRQOL loss, and knowledge about the relationship between visual field loss and HRQOL should have a function in treatment decisions. Several aspects of this relationship are clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…More relevant, however, is the fact that visual field loss is related to vision and health-related quality-oflife (HRQOL), which directly reflect patients' experiences. [1][2][3][4][5] Ultimately the aim of glaucoma treatment is to prevent HRQOL loss, and knowledge about the relationship between visual field loss and HRQOL should have a function in treatment decisions. Several aspects of this relationship are clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…6,14 However, our systematic review shows that still a considerable number of glaucoma patients become blind or visually impaired at the end of their life. Factors associated with end-of-life visual disability in glaucoma patients are advanced VF loss at diagnosis, 11,12,14 progression of VF loss, 14 noncompliance with treatment, 11 fluctuation of IOP during treatment, 11 higher IOP, 14 presence of PEXG, 11 longer duration of the disease (longer life expectancy), 14 and other eye diseases.…”
Section: Discussionmentioning
confidence: 98%
“…1,2,5 Nerve fiber loss and related VF loss are irreversible but lowering the intraocular pressure (IOP) reduces progression and risk of blindness. 1,6 The goal of eye care is to prevent visual loss and impairment in quality of life. Severe visual loss and blindness have a large impact on patients, health care providers, and society.…”
mentioning
confidence: 99%
“…Yanli Zhu, 1 Lihong Zhang, 1 Jimena F Schmidt, 2 and Jeffrey M Gidday Like all cells, neurons adapt to stress by transient alterations in phenotype, an epigenetic response that forms the basis for preconditioning against acute ischemic injury in the central nervous system. We recently showed that a modified repetitive hypoxic preconditioning (RHP) regimen significantly extends the window of ischemic tolerance to acute retinal ischemic injury from days to months.…”
Section: Glaucoma-induced Degeneration Of Retinal Ganglion Cells Prevmentioning
confidence: 99%
“…Current pharmacological treatments designed to lower intraocular pressure (IOP) in primary open-angle glaucoma have shown some efficacy in delaying or preventing the onset of disease (2), but many eligible patients do not receive regular treatment or derive significant benefit from this approach, and many individuals develop glaucoma in the absence of significant intraocular hypertension. Thus, neuroprotective-based therapeutic approaches to prevent or slow the progressive loss of retinal ganglion cells (RGCs) that characterize this neuropathy have received considerable attention (3,4).…”
Section: Introductionmentioning
confidence: 99%